NILAI-NILAI PENDIDIKAN AKHLAK DALAM KISAH NABI YUSUF AS DAN IMPLIKASINYA PADA PENDIDIKAN AKHLAK DI SEKOLAH - Elis Nur Hasanah; Hunainah Hunainah (QATHRUNÂ, 2019)
This study aims to determine the values ​​of moral education contained in the story of the Prophet Yusuf AS and to know the implications of the values ​​of moral education in the story of the Prophet Yusuf As on moral education in schools. This is based on the fact that the story of the Prophet Yusuf AS in the Koran is one of the best stories that contain educational values. The method used in this research is library research on written texts in books related to moral education, and the story of the Prophet Yusuf AS and its implications for moral education in schools. Data collection was carried out with several literatures or books consisting of primary and secondary data, namely: 1) Primary data, taken from Al Quran and tafsir and Hadith, and books about the story of the prophet Yusuf AS. 2) Secondary data, taken from other than Al-Quran and Hadith regarding the stories of the prophet Yusuf AS, namely from dictionaries, books of education and morals, stories of the prophets and so on. The results of this study indicate that the values ​​of moral education in the story of the Prophet Yusuf As include: the value of honesty, the value of faith, the value of responsibility, moral values, and the value of patience, which these values ​​can be used as motivation for moral education in building a personal personality. have a noble character, and make a story not just a story but a lesson value that can be learned and a form of learning strategy in schools where it is not just a story but there are several methods, one of which is the method of preaching through stories.